Case report: Small bowel obstruction secondary to congenital transmesenteric internal hernia in a cat - Kang, Min-Hee; Kang, Young-Chil; Yoon, Jun-Won; Park, Hee-Myung (Frontiers in Veterinary Science, 2024)
An 8-month-old castrated male British Shorthair cat presented with acute anorexia and vomiting. The overall clinical presentation included generalized depression. Physical examination revealed palpable abdominal mass, thus foreign body or intussusception was suspected. Abdominal radiographs showed segmental dilation of small intestine and ultrasonography revealed target lesion with dilated small bowel loops and disrupted normal wall layering, suggestive of intussusception. Exploratory laparotomy confirmed congenital mesenteric defects associated with small intestinal obstruction. Surgical intervention involved dissection, ligation of encircling blood vessels, and closure of mesenteric defects. The cat was discharged after three days, exhibiting normal postoperative recovery. To our knowledge, this is the first case report of congenital mesenteric defect associated with small intestinal obstruction in a cat. While internal hernias are rare, it is essential to include them in the differential diagnosis for cases of intestinal obstruction, particularly in patients with no history of previous surgery or trauma. The potential for strangulation and ischemia in the affected loops elevates internal hernias to a critical, life-threatening condition, emphasizing the need for prompt recognition and urgent surgical intervention as an emergency.